Reconsidering college : Christian higher education for working adults - Ostrander, Richard, 1965- (Abilene Christian University Press, 2014)
A simple, clear introduction to higher education from a Christian perspective for the adult student. More and more adults are seeking to develop themselves and improve their professional opportunities by completing a college degree. Whether business professionals, salespersons, nurses, parents, or persons engaged in any other profession, many working adults recognize the value of furthering their education. And more and more universities are providing special degree tracksfor such non-traditional students. This book is designed to help all of those who are "reconsidering college" to understand the value of adult education and explain some ways that suchan education can be distinctively Christian. It addresses important topics for the Christian adult student, such as: - The purpose and value of work from a Christian perspective. - The practical and intrinsic value of education for working adults. - Christian worldview and adult education: What difference does it make? - Integrating faith, learning, and living in the professional world